Hemobilia from a right hepatic artery pseudoaneurysm due to chronic cholecystitis. (August 2019) - Das, Manjusha; Volmar, Fritz-Henry; Walayat, Saqib; Nolte, Ryan
Splanchnic pseudoaneurysms are rare causes of hemobilia. Specifically, hepatic artery pseudoaneurysms from infectious or inflammatory etiology are even more rare. In this article, we describe our encounter with a 72-year-old female presenting with obstructive jaundice and acute blood loss anemia. Upper endoscopy indicated hemobilia and endoscopic retrograde cholangiopancreatography was completed with stent in place. Post endoscopic retrograde cholangiopancreatography, computed tomography angiogram indicated a right hepatic artery pseudoaneurysm which was the cause of her hemobilia. The patient was ultimately treated with selective coil embolization and interval cholecystectomy.